MOBILE APPLICATION FOR DEVELOPING SPEAKING SKILLS: A BIBLIOMETRIC REVIEW - Kudaibergen A. A.; Akmadi M.A. (Foundations and Trends in Modern Learning, 2025)
This study investigates the evolution, effectiveness, and pedagogical impact of mobile applications for developing English speaking skills across two distinct five-year periods: 2015-2019 and 2020-2025. Using a comparative bibliometric analysis of 200 Scopus-indexed publications, the research identifies major technological, methodological, and conceptual shifts in Mobile-Assisted Language Learning. The findings show that interest in speaking-oriented mobile tools has grown exponentially since 2019, marked by an increase in annual publications, citation rates, and global research activity, particularly across Asian countries. Cluster analysis (green, red, and blue clusters) reveals three dominant research directions: (1) educational technologies and mobile learning practices, (2) human-centered digital applications, and (3) cognitive and linguistic approaches to speech development. Comparative results indicate a clear transition from early experimental mobile apps to advanced AI-driven systems offering real-time feedback, adaptive learning, and conversational interaction. Despite challenges related to technological limitations, contextual feedback, and pedagogical integration, mobile applications consistently demonstrate positive effects on students’ speaking fluency, motivation, autonomy, and communicative competence. The study contributes an evidence-based understanding of how mobile learning tools have transformed speaking instruction over the past decade and highlights promising future directions for integrating intelligent mobile technologies into language pedagogy